Time Collapse in Social Media: Extending the Context Collapse. (March 2018) - Brandtzaeg, Petter Bae; Lüders, Marika
Context collapse, or the flattening of multiple audiences into a single context, has been an important notion in research on privacy experiences, self-performance, and changing user practices in social media. Yet, previous research has mainly addressed context collapse in spatial rather than temporal terms. The resulting lack of an understanding of time in social media limits our conception of the social media context. The aim of this article is therefore to go beyond the spatial dimension in the current notion of "context collapse" in social media. We discuss relevant theories, empirical evidence, and technical features that address the importance of a time dimension and suggest a collapse of temporal patterns in social media. By introducing the concept of "time collapse, " we account for how context in social media may muddle the time boundary between past and present, which, in turn, can affect how users manage their identity and performance on social media. Whereas research on social media has commonly addressed self-performance and impression management, we understand self-identity as an entity in progress. We analyze the results of two empirical case studies to suggest how and why a collapse of time related to self-performance is becoming increasingly prevalent, focusing on young people and Facebook. Our analyses contribute to a new understanding of time and the prolonged self-documenting practices typical of social media. Our research offers a unique understanding of the nature and conceptualization of time that may guide future directions in the study of social media and their implications for young people.